2007
DOI: 10.1007/s00040-007-0964-3
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Interspecific competition among ants in the boreal forest: Testing predictions from a linear hierarchical competition model

Abstract: Competitive interactions often play an important role in local community structure, and particularly so in ant communities. We test predictions derived from a competition model proposed for Scandinavian ant communities by comparing ant nest densities inside and outside fifty randomly-selected territories of competitively dominant wood ants within 30 km of Umeå, northern Sweden. As predicted by the model, competitively-intermediate encounter species, as well as other territorial species, showed complementary oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Recent studies have Psyche revealed that F. fusca is one of the most frequent plesiobionts among the studied ants. Similarly to other common plesiobionts, F. fusca is also a submissive species in the three-level classification of the competitive hierarchy in ants [51,52]. The submissive behaviour and the opportunistic character of this species can be considered as one of the main features that contribute to its frequent cooccurrence with other species in plesiobiotic associations.…”
Section: Significance Of Differences Between Plesiobiotic Partnersmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have Psyche revealed that F. fusca is one of the most frequent plesiobionts among the studied ants. Similarly to other common plesiobionts, F. fusca is also a submissive species in the three-level classification of the competitive hierarchy in ants [51,52]. The submissive behaviour and the opportunistic character of this species can be considered as one of the main features that contribute to its frequent cooccurrence with other species in plesiobiotic associations.…”
Section: Significance Of Differences Between Plesiobiotic Partnersmentioning
confidence: 99%
“…Contrary to the afore-mentioned species, several Camponotus species are typically regarded as encounter species that is, they defend not only their nests but the discovered resources as well [51,52]; therefore only submissive species can be expected to be their plesiobiotic partners.…”
Section: Significance Of Differences Between Plesiobiotic Partnersmentioning
confidence: 99%
“…One possible reasons for the carpenter ants' distance from more sunny places is the reduction of competition with other ant species. One of the indications that can explain our results is that carpenter ants encounter species that do not defend their territory [42] and avoid forests with wood ants with large territories [43]. It is possible that carpenter ants can compensate for poorer temperature conditions due to their endosymbiosis with the Blochmannia bacteria, which improves colony growth and immune defense [44,45].…”
Section: Discussionmentioning
confidence: 98%
“…Thus, in much colder regions than the Mediterranean (i.e., boreal and alpine), where habitat heterogeneity is low and the abundance of behavioral ant dominant species is high, the biotic filter might play a more relevant role and thus competition might be the predominant force structuring local ant communities. [56][57][58][59]. Still, the role of competitive exclusion in the ant low-diversity systems typical from boreal and alpine forests remains unclear (39).…”
Section: Mediterraneanmentioning
confidence: 99%